Efficacy of a school-based obesity prevention intervention at reducing added sugar and sodium in children's school lunches: the LA Health randomized controlled trial. Issue 11 (November 2018) - Hawkins, Keely; Burton, Jeffrey; Apolzan, John; Thomson, Jessi; Williamson, Donald; Martin, Corby
Abstract Background Decreasing selection and consumption of sodium and added sugars in the school cafeteria setting is important to provide optimal nutrition to children. Objective The ofjective of this study is to determine whether Louisiana (LA) Health, a school-based obesity prevention intervention, could successfully reduce children's selection and consumption of sodium and added sugars during school lunches vs. the control group. Design Food selection, consumption, and plate waste from student lunches (3 consecutive days) in 33 public schools in rural Louisiana were collected and analyzed using the digital photography of foods method at baseline and after a 28-month obesity prevention intervention (LA Health) beginning in 4th–6th grade (87% of children received free or reduced cost lunch). Selection and consumption of energy, added sugar, and sodium was objectively measured using digital photography of foods. Mixed models, including Race and BMI, were used to determine whether change in selection and consumption differed by group. Results Sodium decreased for selection (− 233.1 ± 89.4 mg/lunch, p  = 0.04) and consumption (− 206.3 ± 65.9, mg/lunch) in the intervention (vs. control) by month 18, and in consumption by month 28 (− 153.5 ± 66.9 mg/lunch, p  = 0.03). Change in added sugar consumption decreased in the intervention (vs. control) at month 18 (− 3.7 ± 1.6, p  = 0.05) and at month 28 (− 3.5 ± 1.6 tsp/lunch, p  = 0.05). Conclusions LA Health decreased the amount of added sugar and sodium selected and consumed, but not plate waste, by month 28. Results highlight the importance of long-term interventions and policies targeting provision and selection to improve dietary patterns in children, with less focus on plate waste.